Halal governance system based on Islamic Philanthropy in universities, pesantren, and hospitals in Central Java - A. Zaenurrosyid, A. Zaenurrosyid; Adil Liaqat, Adil Liaqat; Hidayatus Sholihah, Hidayatus Sholihah (Halal Studies and Society, 2025)
The development of halal industry in Indonesia is not only part of the global Sharia economic dynamics but also shows that Muslims are becoming more aware of the importance of halal assurance in all areas of life. As demand increases for a comprehensive halal system, including in education, religious boarding schools, and healthcare services, the need to manage these systems professionally has become increasingly important. A strategic method worth exploring is the integration of halal governance with Islamic philanthropic practices, which hold immense potential in supporting the sustainability of Islamic institutions. A compelling case study was Sultan Agung Islamic University (UNISSULA) in Semarang, a waqf-based university with an integrated ecosystem that includes higher education institutions, student pesantren (Islamic boarding houses), and the Sultan Agung Islamic Hospital (RSI SA). Therefore, this study aims to investigate halal governance model based on Islamic philanthropy in UNISSULA environment, treating the university, pesantren, and hospital as an interconnected ecosystem. To achieve this objective, a qualitative with a case study method and a multidisciplinary perspective were used, combining Islamic law and halal system management. Data were collected through in-depth interviews, participatory observations, and documentation, involving university lecturers, and healthcare professionals at RSI SA. The results showed that halal governance model at UNISSULA was strongly supported by structured and institutionalized Islamic philanthropic values. Therefore, the synergy between halal systems and Islamic philanthropy could foster institutions that was competitive, accountable, and oriented toward public welfare (maslahah).